BERPIKIR POSITIF DAN PENERIMAAN DIRI PADA REMAJA PENYANDANG CACAT TUBUH AKIBAT KECELAKAAN - Tentama, Fatwa (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
The purpose of this research was to examine empirically the relationship between positive thinking and self acceptance. Subjects were adolescences, aged 18-24 years old who have physical defect caused by accident. Data collecting by self-acceptance scale and positive thinking scale. Data analysis used product moment correlation from Pearson. Data analysis showed the coefficient correlation between positive thinking and self acceptance, r =0.696 and p = 0.000 (p<0.01). It means there is significantly positive relationship between positive thinking and self-acceptance on the adolescences that have physical defect caused by accident. The higher positive thinking, the higher self-acceptance of the adolescences that have physical defect caused by accident will be. The lower positive thinking, the lower self-acceptance of the adolescences that have physical defect caused by accident will be. Positive thinking gives effective contribution to self-acceptance as well as 48.4 %. The rest 51.6% are from other variables that influence self-acceptance.